2013-05-17 14:48:21 UTC
ln (x – 2) + ln (x + 2) = ln 5
When I solve it I always get either a negative and therefore non-real answer or 3.
When I plug 3 back into the equation: BAM! Doesn't work.
This time I'm gonna show my work so if possible you peeps can write a critique... :D
Here's how I fail:
ln (x – 2) + ln (x + 2) = ln 5
Now I multiply inside the parenthesis...
ln(x^2-4)=ln(5)
Divide both sides by ln()
x^2-4=5
add 4 to both sides
x^2=9
square root of both sides
x=3
Checking my work:
ln (3 – 2) + ln (3 + 2) = ln 5
1.609436912=1.609436912
Wait what? I got it right... but it was wrong just a minute ago...
XD
Ok peeps, instead of answering that for 10 points answer this:
What color is Itachi Uchiha's ring?